Cultural Equivalence Translation: Revealing the Intercultural Bataknese, Indonesian and English Proverbs - Jepri (Faculty of Letters Universitas Balikpapan, 2023)
The significance of cultural equivalence translation in showing the cross-cultural meanings and values ingrained in English, Indonesian, and Bataknese proverbs is discussed in this article. The beliefs, values, and worldviews of the communities who produce proverbs are reflected in them, making proverbs an essential source of cultural information. Proverbs frequently make use of idiomatic terms, metaphors, and references that are culturally specific, making it difficult to translate them from one language to another. The focus analysis of proverbs from Bataknese, Indonesian and English to underline 1) the significance of comprehending the cultural setting in which these proverbs are created and employed. 2) The underlying meanings and values of these proverbs can be discovered, as well as the ways in which they represent the attitudes and beliefs of their distinct cultures, through the process of cultural equivalence translation. This paper applies the Cultural Equivalence Translation theory to reveal the intercultural of the proverbs and descriptive analysis method. This study finds that the potential of proverb study to 1) increase intercultural understanding and communication, 2) improve language learning, and 3) contribute to a more inclusive, tolerant, and 4) peaceful global community.